2020
DOI: 10.14710/j.gauss.v9i3.28915
|View full text |Cite
|
Sign up to set email alerts
|

Perbandingan Metode Smote Random Forest Dan Smote Xgboost Untuk Klasifikasi Tingkat Penyakit Hepatitis C Pada Imbalance Class Data

Abstract: Hepatitis causes around 1.4 million people die every year. This number makes hepatitis to be the largest contagious disease in the number of deaths after tuberculosis. Liver biopsy is still the best method for diagnosing the stage of hepatitis C, but this method is an invasive, painful, expensive, and can cause complications. Non-invasively method needs to be developed, one of non-invasif method is machine learning. Random Forest and XGboost are classification methods that are often used, since they have many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
17

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 2 publications
0
9
0
17
Order By: Relevance
“…One of the oversampling methods that can be used is the Synthetic Minority Oversampling Technique (SMOTE). The SMOTE method adds the amount of data from the minor class using the neighbor approach to make it equal to the major class [17]. In the case of credit scoring classification, the SMOTE method results in an accuracy value of 81.69%, which is relatively high; this value is better than other methods [18].…”
Section: Synthetic Minority Oversampling Technique (Smote)mentioning
confidence: 99%
See 2 more Smart Citations
“…One of the oversampling methods that can be used is the Synthetic Minority Oversampling Technique (SMOTE). The SMOTE method adds the amount of data from the minor class using the neighbor approach to make it equal to the major class [17]. In the case of credit scoring classification, the SMOTE method results in an accuracy value of 81.69%, which is relatively high; this value is better than other methods [18].…”
Section: Synthetic Minority Oversampling Technique (Smote)mentioning
confidence: 99%
“…Cross-validation is a computer-intensive technique used to evaluate the performance of an algorithm model and the prediction error using all available examples as training and testing examples [17,28,29]. K-Fold Cross Validation was the method used in this study.…”
Section: Cross Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Untuk meningkatkan akurasi pada random forest dengan melakukan hyperparameter diantaranya n_estimators dan max_depth. Parameter n_estimators ini yang akan menetukan berapa decission tree yang akan dibuat, sedangkan max_depth menyatakan seberapa dalam layer setiap decission tree akan dibuat (Syukron, Santoso, & Widiharih, 2020;Zhang, Yang, & Zhou, 2018). Tabel 7 adalah ringkasan pengaturan hyperparameter RF.…”
Section: Gambar 2 Feature Corellationunclassified
“…In [6], concluded that a hybrid method can increase AUC gradually with an increase in the percentage of oversampling. Related research was also conducted [15] by comparing SMOTE Random Forest and SMOTE XGBoost models on the HCV dataset. The results obtained that models with SMOTE can significantly increase the recall value from under 2% to more than 70%.…”
Section: Introductionmentioning
confidence: 99%